1986
DOI: 10.1002/jez.1402400105
|View full text |Cite
|
Sign up to set email alerts
|

Contractile responses to temperature in the locomotory musculature of striped bass Morone saxatilis

Abstract: The effects of temperature on contractile function of isolated, chemically skinned red (slow oxidative) and white (fast glycolytic) fibers of skeletal muscle from thermally acclimated striped bass (Morone saxatilis) were determined. Acclimation to 10" or 25°C has no significant effect on maximum isometric tension (Po) or maximum unloaded contraction velocity (V,) of fibers Dr. Moerlands current address is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…T t depends not only on the experimental conditions but also on whether Ca 2+ -regulatory proteins are present. The Arrhenius plot of fish myofibrillar ATPase at saturating Ca 2+ exhibited a discontinuity [ 68 ], while this was not the case for in vitro motility sliding speed and actin-activated MgATPase activity with fish myosin and unregulated F-actin [ 69 ]. For regulated thin filaments, Homsher et al [ 16 ] reported a break in the Arrhenius plot around 12.5°C that was not observed for unregulated F-actin within the 7–25°C temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…T t depends not only on the experimental conditions but also on whether Ca 2+ -regulatory proteins are present. The Arrhenius plot of fish myofibrillar ATPase at saturating Ca 2+ exhibited a discontinuity [ 68 ], while this was not the case for in vitro motility sliding speed and actin-activated MgATPase activity with fish myosin and unregulated F-actin [ 69 ]. For regulated thin filaments, Homsher et al [ 16 ] reported a break in the Arrhenius plot around 12.5°C that was not observed for unregulated F-actin within the 7–25°C temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…The Arrhenius plot is well fit by a single, least-squares, linear skinned, fast-twitch fibers from the bulltrout (Johnston and Sidell, 1984), but approximately 30% greater than observed Normalized Force (% o Vi) for fast-twitch fibers from a different teleost, the striped bass (Moerland and Sidell, 1986). We note that there is a downiortening velocity at varying [Vi] (10 puM-1 mM) normal-ward concavity in the present data for temperatures <150C St to that obtained in the absence of Vi versus normalized (lower temperatures to right of Fig.…”
Section: C Omentioning
confidence: 90%
“…Furthermore, physiologically relevant variations in viscosity likely influence motility of ectotherms. In particular, certain species of fish may experience significant changes in temperature, with concomitant changes in cytoplasmic viscosity (see above) and thus changes in the speed and energy requirements for swimming (Moerland and Sidell, 1986).…”
Section: Shortening Velocitymentioning
confidence: 99%